Evaluation of Financial Management in Improving the Quality of Education at MA Al-Amin Islamic Boarding School - Mohzana, Mohzana; Mas'ulil Munawaroh, Mas'ulil; Kasiani, Kasiani; Kartiko, Ari; Rofiq, Ainur (Universitas Muhammadiyah Ponorogo, 2024)
Evaluation is the most important stage of financial management. Evaluation of financial management has an influence on improving the quality of education starting from the quality of input, process and output. Based on this phenomenon or problem, researchers are interested in researching the evaluation of financial management in improving the quality of education at MA Al-Amin Islamic Boarding School Mojokerto. Based on this background, the objectives of this research are as follows: 1) To determine financial supervision at MA Al-Amin Islamic Boarding School Mojokerto. 2) To find out the form of financial accountability at MA Al-Amin Islamic Boarding School Mojokerto. This research uses descriptive qualitative research with a case study approach, to collect data researchers use observation, interview and documentation techniques. The results of this research are: evaluation of financial management in improving the quality of education at MA Al-Amin Islamic Boarding School Mojokerto manages finances very well by conducting routine and ongoing financial evaluations to be able to improve the quality of educational supporting facilities and infrastructure, namely in the form of developing digital media, among others. others are ADILS (Al-Amin digital Learning system), ALIMS (Al-Amin Library management system), as well as non-cash based transactions A-Cash and A-Smart.